Production and Purification of Polyclonal Antibodies Against Recombinant BoNT/A-HcC Domain for Sandwich ELISA Detection of BoNT/A: Detection of BoNT/A by Sandwich ELISA - Sameie Abianeh, Hossein; Nazarian, Shahram; kordbacheh, Emad; Felegary, Alireza (Iranian Journal of Pharmaceutical Sciences, 2024)
Botulinum neurotoxin (BoNT), a lethal bacterial toxin causing neuroparalytic disease, necessitates robust detection methods to prevent and manage botulism outbreaks. The receptor-binding domain of the toxin’s heavy chain (Hc) has been extensively explored as a potential BoNT vaccine candidate. This study’s primary goal is the swift detection of Botulinum neurotoxin type A (BoNT/A) using a sandwich ELISA method employing polyclonal antibodies. The recombinant BoNT/A-285HcC was induced with one mM IPTG at 25°C for 18 hours to reduce inclusion bodies and purified using Ni-NTA under non-denaturing conditions. Immunization of animals followed a specific regimen using purified BoNT/A-285HcC recombinant antigen and Freund’s adjuvant. IgG antibodies from immunized mice serum were isolated using protein G resin. The purified antibodies’ reactivity with recombinant BoNT/A-285HcC protein was assessed through western blotting. Efficient protein expression was achieved, yielding 50 mg/L. The recombinant BoNT/A-285HcC, with a molecular weight of 46 kDa, was purified with a near 90% purity level. ELISA results demonstrated a significant rise in anti-BoNT/A antibody titers following three doses. Western blot analysis confirmed the specific binding capability of the purified anti-BoNT/A IgG. Ultimately, the sandwich ELISA developed in this study exhibited the ability to detect 100 pg/ml of BoNT/A, utilizing 1.25 µg/ml of mice antibody as the capture and 0.3 µg/ml of rabbit antibody as the detection antibody. Purified polyclonal antibodies against recombinant BoNT/A-285HcC can be effectively employed in diagnostic serological tests for BoNT/A detection, with a limit of detection (LOD) of 100 pg/ml, significantly enhancing our ability to combat BoNT-related threats and ensuring the safety of medical applications.